Immersive Anatomy Atlas: Learning Factual Medical Knowledge in a Virtual Reality Environment. Issue 2 (30th June 2021) - Gloy, Kilian; Weyhe, Paul; Nerenz, Eric; Kaluschke, Maximilian; Uslar, Verena; Zachmann, Gabriel; Weyhe, Dirk
Abstract : In order to improve learning efficiency and memory retention in medical teaching, furthering active learning seems to be an effective alternative to classical teaching. One option to make active exploration of the subject matter possible is the use of virtual reality (VR) technology. The authors developed an immersive anatomy atlas which allows users to explore human anatomical structures interactively through virtual dissection. Thirty‐two senior‐class students from two German high schools with no prior formal medical training were separated into two groups and tasked with answering an anatomical questionnaire. One group used traditional anatomical textbooks and the other used the immersive virtual reality atlas. The time needed to answer the questions was measured. Several weeks later, the participants answered a similar questionnaire with different anatomical questions in order to test memory retention. The VR group took significantly less time to answer the questionnaire, and participants from the VR group had significantly better results over both tests. Based on the results of this study, VR learning seems to be more efficient and to have better long‐term effects for the study of anatomy. The reason for that could lie in the VR environment's high immersion, and the possibility to freely and interactively explore a realistic representation of human anatomy. Immersive VR technology offers many possibilities for medical teaching and training, especially as a support for cadaver dissection courses.